2017
DOI: 10.1186/s13287-016-0460-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunoselected STRO-3+ mesenchymal precursor cells reduce inflammation and improve clinical outcomes in a large animal model of monoarthritis

Abstract: BackgroundThe purpose of this study was to investigate the therapeutic efficacy of intravenously administered immunoselected STRO-3 + mesenchymal precursor cells (MPCs) on clinical scores, joint pathology and cytokine production in an ovine model of monoarthritis.MethodsMonoarthritis was established in 16 adult merino sheep by administration of bovine type II collagen into the left hock joint following initial sensitization to this antigen. After 24 h, sheep were administered either 150 million allogeneic ovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Additionally, a slight infiltration of the synovial tissues with CD4þ lymphocytes and CD14þ monocytes or macrophages was observed. All these findings were contrary to those observed in the control animals (Abdalmula et al 2017). Similar results were reported in another model of induced OA (medial meniscectomy and ACL resection) treated with an intra-articular implantation of different doses of allogenic AD-MSCs and HA 6 weeks after the surgery.…”
Section: Msc Studies In Sheepsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, a slight infiltration of the synovial tissues with CD4þ lymphocytes and CD14þ monocytes or macrophages was observed. All these findings were contrary to those observed in the control animals (Abdalmula et al 2017). Similar results were reported in another model of induced OA (medial meniscectomy and ACL resection) treated with an intra-articular implantation of different doses of allogenic AD-MSCs and HA 6 weeks after the surgery.…”
Section: Msc Studies In Sheepsupporting
confidence: 84%
“…Numerous studies on the repair of osteochondral ailments using MSCs have been conducted in sheep. Most of the studies (listed in Table 1) have reported the usefulness of MSCs for improving the condition of joint ailments compared to that of the control (Guo et al 2004;Feitosa et al 2010;Zscharnack et al 2010;Al Faqeh et al 2012;Caminal, Fonseca, et al 2014;Song et al 2014;Garcia et al 2014;Zorzi et al 2015;Desando et al 2016;Whitehouse et al 2017;Abdalmula et al 2017;Feng et al 2018). In addition to cultured MSCs, the BM aspirate too has been reported to improve cartilage healing (Duygulu et al 2012).…”
Section: Msc Studies In Sheepmentioning
confidence: 99%
“…In the inflamed joints, there was a marked reduction in inflammatory macrophages and significantly reduced levels of the proinflammatory cytokines TNF-α and IL-6. 70,71…”
Section: Mpcs In Advanced Chronic Hfref Patients: Is There Biologic Pmentioning
confidence: 99%
“…Moreover, co-culture of human synovial and cartilage explants exposed to conditioned media from MSC pre-treated with TNF-alpha showed reduced expression of IL-beta and matrix metalloproteinases and upregulation of the cytokine signalling suppressor 1 gene while, in cartilage, upregulation of IL-1 receptor antagonist and downregulation of the proteoglycan degrading proteinase ADAMTS-5 was observed [ 51 ]. MPCs injected intravenously to sheep with collagen-induced joint inflammation was demonstrated to decrease cartilage erosions, synovial stromal cell activation, angiogenesis, and plasma levels of activin A and IL-17A, confirming that systemic administration of these cells can modulate both local joint and systemic inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…Our previous preclinical studies using ovine models of post-traumatic OA [ 30 ] and collagen-induced arthritis [ 31 , 32 ] have demonstrated the safety and efficacy of allogeneic STRO-3 + -selected MPCs in preserving synovial joint articular cartilage, downregulating pro-inflammatory cytokine activities, and preserving cartilage and endothelial cell function. These encouraging preclinical findings using allogeneic STRO-3 + MPCs provided the rationale for our hypothesis that these cells were safe and might provide long-term clinical and joint structural benefits when administered to patients after ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%